Investment Risk Management of Bulk LPG Filling Station (SPBE) Construction Project In Sorong - Irawadi, Ichwal; Jahroh, Siti; Ramadyanto, Widodo (Pelopor Publikasi Akademika, 2024)
The Sorong region is known as a natural gas producer in Indonesia, but the local community has not been able to enjoy the gas product, namely LPG, at the same price as on the island of Java or other regions. Investment opportunities to build SPBE in Sorong are very attractive and open very wide. This study aims to analyze the risks that can affect investment in the project. This study uses types and sources of data in the form of primary data in the form of opinions and experiences derived from the results of interviews and Forum Group Discussion (FGD). The results of the analysis showed that 3 sources of risk were in the very high category, 22 sources of risk were in the high category, 35 sources of risk were in the medium category, 13 sources of risk were in the low to medium category, and 10 sources of risk were in the low category. After being given recommendations for the risk control process, it is estimated that 2 risks are still in the high category and 7 other sources of risk have been successfully downgraded to the medium category. At the planning stage, it is necessary to pay attention to the lack of commitment to gas volume and supply. At the EPC stage, material delays due to community disturbances, land execution, and work accidents need to be dealt with seriously.